Kerapatan Stomata pada Daun Mangga (Mangifera indica) di Kawasan PT Semen Gresik Pabrik Tuban Kecamatan Kerek Kabupaten Tuban - Hidayat, Achmad Nur; Mustofa, Ali; Cintamulya, Imas (Jurnal Biologi Universitas Andalas, 2024)
The purpose of this study was to determine the density of stomata and stomatal structure on Mango leaves in each ring of the cement factory area. The research is descriptive analysis. Sampling was done through a random survey in the Indonesian cement industry Tuban factory which was divided into 3 rings, namely Ring 1 Ring 2 and Ring 3. The parameters observed were stomatal density and damage. The results showed that the density of stomata in Ring 1 showed a percentage of 0.162 which showed a low density while Ring 2 was 371, 91 which showed a medium density and Ring 3 was 449.07 which showed a medium density. The results presented in Table 2 on the level of stomatal damage show a difference in the percentage of stomatal damage on mango leaves (Mangifera indica) located in Ring 1 and Ring 2. In stomata in Ring 1 with a greater percentage of stomatal damage, which is 34.7% compared to stomatal damage to mango leaves located in Ring 2 by 20.7% and Ring 3 by 11%. The conclusion of this study shows that the density and damage to the stomata of mango leaves (Mangifera indica) can be influenced by the concentration of pollutants. the level of density and stomatal damage in the Semen Indonesia Tuban area shows that the closer to the factory area the higher the level of air pollution which causes the nearest area to have high stomatal damage and high stomatal density.